Magnetic graphene oxide as a platform for the immobilization of cellulases and xylanases: Ultrastructural characterization and assessment of lignocellulosic biomass hydrolysis. (February 2021) - Paz-Cedeno, Fernando Roberto; Carceller, Jose Miguel; Iborra, Sara; Donato, Ricardo Keitel; Godoy, Anna Paula; Veloso de Paula, Ariela; Monti, Rubens; Corma, Avelino; Masarin, Fernando
Abstract: For producing second-generation ethanol (cellulosic ethanol) and other value-added bioproducts, magnetic graphene oxide (GO-MNP) was synthesized in this work and used as the immobilization support for an industrial cellulase-and xylanase-containing preparation. GO-MNP characterization by TEM, SEM and ATR-FTIR spectroscopy showed that the magnetic nanoparticles are homogeneously distributed onto the GO sheets surface. The enzymatic preparation was immobilized by means of carbodiimide cross-linking chemistry using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N -hydroxysuccinimide (NHS). The supported final biocatalyst (GO-MNP-Enz) showed high activity for the hydrolysis of pretreated sugarcane bagasse (PSB) and presented relative endoglucanase, xylanase, β-glucosidase, and β-xylosidase activities of 70%, 66%, 88%, and 70%, respectively, after 10 cycles of hydrolysis of their respective substrates. The biocatalyst also maintained approximately 50% and 80% of its efficiency for cellulose and xylan hydrolysis, respectively, being the TOF (g.g −1 .h −1 ) the highest observed when compared with previous results reported in literature. These findings suggest that GO-MNP-Enz may be a prospective candidate for industrial applications such as second-generation ethanol production. Graphical abstract: Image 1 Highlights: Enzymes immobilized onto graphene oxide-magnetite form a stable biocatalyst. The ultrastructural characterization of the magnetic biocatalyst is presented. The biocatalyst has all enzymatic activities to hydrolyze lignocellulosic biomass. A high turnover frequency is reached after several hydrolysis cycles. Magnetic separation allows easy recycling of the biocatalyst.